Preliminary development of mini anechoic chamber - Hasnain, A.; Imran, M.I.; Rohaiza, Z.S.; Roslan, S.; Takiyuddin, A.A.; Rusnani, A.; Azremi, Abdullah Al Hadi (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org